121 PTTG1: AN IMMUNOLOGIC TARGET FOR MULTIPLE MYELOMA. Issue 1 (1st January 2007) - Ferrari, R.; Prabhakar, M.; Yu, Y.; Grizzi, F.; Jenkins, M. R.; Frezza, E. E.; Hardwick, F.; D'Cunha, N.; Cobos, E.; Chiriva-Internati, M.
Abstract : Purpose: Multiple myeloma (MM) is a malignant B plasma cell cancer that produces abnormal antibodies and proliferates uncontrollably. Due to relapse and nonspecificity of chemo-/radiotherapy and stem cell transplantation, immunotherapy is more specific and may induce long-term immunity. New targets are needed to develop antitumor treatments. Recently, the pituitary tumor transforming gene 1 ( PTTG-1 ) was shown to be a novel oncogene. It is involved in transcriptional and cell cycle regulation, is highly expressed in testis and lowly in normal colon, lung, thymus, and placenta, and is undetectable in normal tissues. It is overexpressed in pituitary adenomas, breast, lung and GI cancers, leukemia, and lymphomas and is associated with tumorigenesis, angiogenesis, and cancer progression. We investigated the presence/rate of expression of PTTG1 in MM patients. Methods: In this study, we analyzed the PTTG1 expression at the protein level by immunocytochemistry in 19 MM patients. Nineteen cytospins, carrying 10 5 MM cells each, were prepared: 14 permeabilized (in 1% Triton 100× in PBS 1×) and 5 unpermeabilized. Cytospins were treated for 15 minutes in 3% H2 O2 and then exposed for 1 hour to 1:60 diluted anti-PTTG-1 antibody (Zymed, San Francisco, CA) and covered for 30 minutes with Envision secondary antibody (Dako, Carpinteria, CA). The primary/secondary antibody reaction was evaluated with DAB staining system (Dako). Summary: PTTG-1 was detectable in 5 of the 19 patients, giving evidence of a 26.3% rate of expression. Three permeabilized and two unpermeabilized samples were immunopositive. Specifically, 21.4% of the samples showed cytoplasmic expression, whereas 40% showed PTTG-1 protein expression on the cellular surface. Conclusion: This study gives interesting insights into the use of PTTG-1 as a suitable target for immunotherapy in MM patients.